Opportunities and Challenges of Economic Development in Malaysia’s Rural Areas - ANAK EDIRIN, ELLFRELSTERN (Trends in Undergraduate Research, 2018)
Rural areas play traditionally important role for our economy as well maintaining social stability. Most of the development is entirely dependent on natural resources in the area which is specialized in a limited number of industries such as agriculture, livestock, forestry, fisheries and local tourism. People that live in rural areas have fewer choices in the social and economic terms. They are facing many problems such as low income, unemployment, low quality of social services like education and healthcare. In addition, remoteness from major urban centres is also one of the problems which is implying the need for well-developed transport infrastructure to support economic development. As stated in the Eleventh Malaysia Plan, the Malaysian Government is committed to ensuring equitable opportunities for all segments of society. Keywords: Development, economic, Eleventh Malaysia Plan, rural